Imperial Cities and Recent Research Trends: Nostalgia, Water Infrastructure, and Segregation - Obertreis, Julia (Imperial Cities in the Tsarist, the Habsburg, and the Ottoman Empires, 2023)
This chapter offers a résumé and outlines three further fields of research that could profit from a focus on imperial cities. The first field is memory of empire and its transformation at historical turning points, such as the inter-war period and the year 1989. The history of re-naming streets or entire cities, the destruction or repurposing of buildings such as churches, and especially the public discussions about monuments can give valuable insight into how memories of empire and specific forms of nostalgia develop. Second, environmental and infrastructural history could gain new insights by directing their attention to imperial cities. All empires tried to gain legitimacy through their policies toward nature and especially water, sometimes sustaining costly infrastructures to harness or overcome natural forces. Third, in the field of urban history proper, segregation and diversity as one central feature of imperial cities should be addressed more directly. Segregation was often tied to larger processes such as industrialization or migration and was thus intricately entwined with economic processes in the housing and job markets. This can be observed on the micro-scale of yards and even inside apartments, which needs more attention.
CRIS-Team Scopus Importer:2024-12-16